Biodegradation of hydrolyzed polyacrylamide by the combined expanded granular sludge bed reactor-aerobic biofilm reactor biosystem and key microorganisms involved in this bioprocess. (September 2018) - Song, Tianwen; Li, Shanshan; Ding, Wande; Li, Haoshuai; Bao, Mutai; Li, Yang
Highlights: HPAM-containing wastewater was treated by the combined EGSB-ABR biosystem. HPAM was used by microorganisms as carbon and nitrogen source. Functional microorganisms was determined by Illumina MiSeq sequencing. The relationship between microbial community and function of bioreactors was linked. Abstract: An investigation was carried out to study the performance of a combined expanded granular sludge bed reactor-aerobic biofilm reactor (EGSB-ABR) biosystem and key microorganisms involved in this bioprocess. When the concentration of hydrolyzed polyacrylamide (HPAM) was 500 mg/L, the maximum removal rate of HPAM reached 64.36%, among which the contribution of the EGSB reactor was 24.35%. Scanning electron microscope (SEM) images and gel permeation chromatography (GPC) analysis showed that macromolecular HPAM was degraded into oligomer with lower molecular weight. Among the key enzymes involved in the degradation of HPAM, laccase had the best tolerance to HPAM. Microbial community structure was analysed by Illumina MiSeq Sequencing, which revealed that Firmicutes, Proteobacteria and Bacteroidetes were the most prevalent bacterial phyla, Trichococcus, Brooklawnia, Bacillus and Pseudomonas were the predominant functional genera, and Methanosaeta was the dominant archaeal genus in the bioprocess. Furthermore, hypothesis about the mechanisms of HPAM biodegradation was proposed.